Assesing Murābaḥah Compliance After Regulatory Reform a Normative Study in Indonesia Sharia Banking - Prayitno, Farrel Izham; Rabbani, Andi Muh Shafwan; Mufiz, Muhammad Alif (ASAS, 2026)
Murābaḥah contracts constitute the most widely used financing instrument in Indonesian sharia banking; however, concerns persist regarding the substantive alignment between contractual practices, DSN-MUI fatwas, and regulatory standards. Although POJK No. 12/POJK.03/2021 was enacted to strengthen sharia governance, systematic post-regulatory assessments of murābaḥah implementation remain limited. This study examines the extent and patterns of disparities in the implementation of DSN-MUI fatwas on murābaḥah contracts in Indonesian sharia banking practices after the enactment of the regulation. The research employs a normative simulation-based approach using secondary data, including DSN–MUI fatwas, Financial Services Authority regulations, and standardized murābaḥah contract documents issued during the 2021-2024 period. A structured normative compliance model was applied to assess four key parameters: ownership transfer, contractual structure, profit margin determination, and risk allocation. The findings show that while formal compliance with regulatory and fatwa provisions has improved in the post-2021 period, substantive sharia compliance remains uneven. Most murābaḥah contracts demonstrate partial compliance, particularly due to deficiencies in ownership transfer and risk-bearing mechanisms, whereas profit margin determination shows relatively higher conformity. These results indicate that murābaḥah is frequently implemented as a financing mechanism rather than as a genuine sale-based contract in accordance with Islamic commercial jurisprudence. Overall, the findings demonstrate that regulatory reform alone is insufficient to ensure substantive sharia compliance without sustained institutional commitment.